Effects of intermittent theta burst stimulation on upper limb motor recovery in early stroke patients: an fNIRS study - Liu, Menghui; Wan, Chunxiao; Wang, Chunyan; Li, Xinyi (Frontiers in Neurology, 2025)
ObjectiveTo explore the recovery of upper limb motor function and the changes in cortical functional connectivity in patients with early subcortical small infarcts accompanied by severe upper limb motor dysfunction (PESSUM) after intermittent theta burst stimulation (iTBS) via functional near-infrared spectroscopy (fNIRS) and to explore the related mechanisms.MethodsWe enrolled 56 subcortical ischemic stroke patients with FMA-UE ≤28 and randomly assigned them to receive either genuine (TG, n = 29) or sham (CG, n = 23) iTBS plus standard rehabilitation over 8 days. fNIRS was used to monitor cerebral HbO, HbD, and HbT concentrations, and RSFC changes were analyzed. The FMA-UE and MBI scores were used to evaluate upper limb motor function and daily activities. Intergroup comparisons were conducted using independent samples t tests, whereas intragroup comparisons were performed using paired samples t tests or Mann–Whitney U tests. The trend of the RSFC changes was analyzed via repeated-measures Analysis of Variance (ANOVA).ResultsBoth groups showed significant improvements in FMA-UE and MBI scores postintervention (p < 0.001). The TG had higher MBI scores than the CG (p = 0.005). fNIRS revealed accelerated cyclical changes in cortical activity in the TG.ConclusioniTBS significantly improved motor function and daily living ability in stroke patients, supporting a role for iTBS in promoting neural repair by accelerating cortical recovery cycles. This study provides evidence that iTBS is an effective rehabilitation strategy poststroke.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=169674, ChiCTR2200060955.